Combination of arrhythmogenic right ventricular dysplasia with left ventricular non-compaction as a special form of cardiomyopathy: clinic, diagnostics, genetic, natural course. (14th October 2021) - Lutokhina, Y A; Blagova, O V; Shestak, A G; Polyak, M E; Bukaeva, A A; Zaklyazminskaya, E V; Varionchik, N V; Sedov, V P; Kogan, E A; Alexandrova, S A; Nedostup, A V
Abstract: Background: A few cases of combination of arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVC) with left ventricular noncompaction (LVNC) have been described. Aims: To study the genetics, diagnostical features and clinical course of the combination of ARVC with LVNC. Materials and methods: 58 patients with ARVC diagnosis (26 men; mean age 39.1±14.2 years; mean follow-up period – 21.5 [6; 60] months) and 125 patients with LVNC (74 men; mean age 46.4±15.1 years; mean follow-up period – 14 [3; 40] months). All patients underwent electrocardiogram (ECG), echocardiography, 24-h ECG monitoring. Heart MRI was performed in 53 (91.4%) patients with ARVC and 60 (48%) with LVNC, heart CT – in 18 (31%) patients with ARVC and 89 (71.2%) with LVNC. For all patients with combination of ARVC and LVNC DNA-diagnostic was performed using both ARVC (PKP2, DSG2, DSP, DSC2, JUP, TMEM43, TGFB3, PLN, LMNA, DES, CTTNA3, EMD, SCN5A, LDB3, CRYAB, FLNC) and LVNC (MYH7, MYBPC3, TAZ, TPM1, LDB3, MYL2, MYL3, ACTC1, TNNT2, TNI3) gene panels. Results: Combination of ARVC and LVNC was found in 9 patients (15.5% of patients form ARVC cohort and 7.2% from LVNC cohort). These patients were distinguished from patients with isolated ARVC or LVNC by aggressive ventricular arrhythmias (frequent premature ventricular beats, sustained ventricular tachycardia, significantly worse antiarrhythmic therapy effect, appropriate shocks of implanted cardioverter-defibrillators (ICD) in all patients with ICD). Patients with combination of ARVC+LVNC were also distinguished from patients with isolated LVNC by the dilatation of RV, low QRS voltage on ECG, presence of AV block, absence of signs of LV hypertrophy on ECG. LV dilatation with reduction of its ejection fraction distinguished patients with mixed cardiomyopathy from patients with isolated ARVC. Potentially pathogenic variants (IV-V classes of pathogenicity) and variants of unclear clinical significance (III class of pathogenicity) were found in both desmosomal and non-desmosomal genes in 78% of patients, including 3 (33%) in DSP gene. Conclusions: The combination of ARVC and LVNC can be caused by mutations in both desmosomal and non-desmosomal genes and has typical features: aggressive, resistant ventricular rhythm abnormalities leading to appropriate ICD shocks and a high risk of sudden cardiac death. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Genetic testing of patients was supported by Grant No. 16-15-10421 of the Russian Science Foundation